Akuntabilitas dan Efektivitas Penggunaan Dana Direktorat Kemahasiswaan Universitas Brawijaya untuk Kegiatan Eksekutif Mahasiswa (EM) Tahun 2023 - Ratna Kartika Tungga Dewi; Dwi Anggarani; Khojanah Hasan (CV. Ulil Albab Corp, 2024)
The Student Executive Board is a student organization within the campus that acts as the executive body at the university level, led by a Student President or Head of the SEB. The SEB often organizes activities funded by the student affairs directorate of Brawijaya University. Accountability is an obligation that demonstrates responsibility, and responsibility yields consequences. These consequences can be in the form of rewards or sanctions, and effectiveness is a measure that indicates how far the targets (quantity, quality, and time) have been achieved. The Student Executive Board is responsible for the funds provided by the student affairs directorate of Brawijaya University. An activity accountability report is one form of accountability and effectiveness report provided by the Student Executive Board. However, there are still many aspects that need to be considered in the supervision of the funding process and its management. The purpose of this study is to analyze the accountability and effectiveness of the use of funds from the student affairs directorate of Brawijaya University for the activities of the Student Executive Board. This study uses qualitative descriptive analysis. The results of the study indicate that the Student Executive Board (SEB) has implemented accountability and effectiveness in the activities carried out and in the reports submitted.